2015
DOI: 10.1002/advs.201500101
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Sensing and Density Functional Theory Study of H2S and SOF2 Adsorption on Au‐Modified Graphene

Abstract: A gas sensor is used to detect SF6 decomposed gases, which are related to insulation faults, to accurately assess the insulated status of electrical equipment. Graphene films (GrF) modified with Au nanoparticles are used as an adsorbent for the detection of H2S and SOF2, which are two characteristic products of SF6 decomposed gases. Sensing experiments are conducted at room temperature. Results demonstrate that Au‐modified GrF yields opposite responses to the tested gases and is thus considered a promising mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
127
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 241 publications
(131 citation statements)
references
References 42 publications
4
127
0
Order By: Relevance
“…As shown in Figure 3, the resistance of the gas sensor significantly reduces when it contacts SF 6 decomposition components [26,27,28,29]. The Ni-CNT gas sensor presents a large gas response to SF 6 decomposition components at room temperature and ambient pressure due to the catalytic property of evenly distributed Ni nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3, the resistance of the gas sensor significantly reduces when it contacts SF 6 decomposition components [26,27,28,29]. The Ni-CNT gas sensor presents a large gas response to SF 6 decomposition components at room temperature and ambient pressure due to the catalytic property of evenly distributed Ni nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, a TiO 2 -based gas sensor usually needs a high working temperature to receive a high gas response to SF 6 decomposition components. It was reported that the LOD of Au-Graphene was only 50 ppm with a gas response of 18.75% to H 2 S [28]. Therefore, the Ni-CNT sensor obviously presents advantages in high gas response and low working temperature.…”
Section: Resultsmentioning
confidence: 99%
“…To detect, evaluate, and diagnose the insulation status of SF 6 gas insulated equipment using the characteristics of SF 6 decomposition, a series of characteristic SF 6 decomposition components, SOF 2 , SO 2 F 2 , SO 2 , H 2 S, CF 4 , HF, and SF 6 , are detected by gas sensors, including metal functionalized single wall carbon nanotubes (SWCNTs) [1][2][3][4][5][6], TiO 2 nanotubes [7][8][9], and graphene gas sensors [10,11], as shown in Table 1. According to the theoretical calculation results, these three kinds of gas-sensing materials are not sensitive to the background gas SF 6 and decomposition component CF 4 .…”
Section: Theoretical Study Comparisonmentioning
confidence: 99%
“…Gas sensors under study for on-line monitoring and fault diagnosis of electrical equipment mainly include carbon nanotube gas sensors [12,13], titanium nanotube gas sensors [14,15], as well as graphene gas sensors [16,17]. Some research results related to GIS partial discharge monitoring field have been achieved [18].…”
Section: Introductionmentioning
confidence: 99%